Impact of droughts on productivity of pearmillet in Rajasthan (MAUSAM, 1986)
The productivity of pearlmillet in Rajasthan during different drought years in the recent decade 1970-79 was studied. It was found that the productivity gets affected considerably as a result of moderate to severe drought conditions in western Rajasthan. The rain water use efficiency of pearl millet was very much less in western Rajasthan compare to eastern Rajasthan.. The study indicates the possibility of improying yield under mild drought conditions in western Rajasthan through better management practices.